Spazi comuni nell’Atene della crisi: il commoning urbano come processo creativo - Volpini, Marco; Frixa, Emanuele (ACME: An International Journal for Critical Geographies, 2017)
Possiamo considerare i commons come forme creative? In relazione a quali processi emerge il loro carattere di novità? Per rispondere a queste domande la creatività dei processi di commoning verrà considerata come il risultato della collettiva esplorazione e implicazione pratica delle persone con i loro ambienti. L’idea di spazi comuni, riformulata a partire dalla prospettiva socio-ecologica di Ingold (2000, 2007, 2011), verrà collegata ai concetti di “soglia” e di “porosità” proposti da Stavrides (2010, 2014), e al discorso sulla creatività culturale come enunciato da Favole (2010), Liep (2001b) e Wagner (1992). A partire da queste premesse teoriche e basandosi sui risultati di un lavoro di campo di due mesi svolto ad Atene nel 2015, l’analisi seguirà tre pratiche di creazione del comune, portate avanti nel corso degli ultimi anni nella capitale greca: il Parco Navarinou, l’Agros Elliniko e il Libero Teatro Autogestito Embros. Il contesto entro cui questi spazi comuni sono emersi è quello di un’esperienza urbana caratterizzata dall’ingiustizia sociale, prodotta dalla forza di striatura (Deleuze e Guattari, 2014) dei poteri economico-amministrativi. È nel confronto con la logica astratta delle striature che gli spazi comuni emergono come forme di creatività collettiva. Common spaces in Athens in times of crisis: urban commoning as a creative process Can we consider the commons as creative forms? Which processes shape their character of novelty? In order to answer these questions, the creativity of the processes of commoning will be considered as the result of the collective exploration and the practical implication of people with their environments. Building on the socio-ecological perspective of Ingold (2000, 2007, 2011), the idea of common spaces will be connected to the concepts of “threshold” and “porosity” in the work of Stavrides (2010, 2014) and the discussion on cultural creativity by Favole (2010), Liep (2001) and Wagner (1992). Based on the results of fieldwork carried in Athens for two months in 2015, the analysis focuses on three practices of creation of the common emerged in the Greek capital in recent years: the Navarinou Park, the Agros Elliniko and the Free Self-Managed Theatre Embros. The context where these common spaces have emerged is a city characterized by social injustice produced by the streak power of economic and managerial elites. Common spaces emerge therefore as forms of collective creativity when facing the abstract logics of streaks. Common spaces in Athens in times of crisis: urban commoning as a creative process Can we consider the commons as creative forms? Which processes shape their character of novelty? In order to answer these questions the creativity of the processes of commoning will be considered as the result of the collective exploration and the practical implication of people with their environments. Building on the socio-ecological perspective of Ingold (2000, 2007, 2011), the idea of common spaces will be connected to the concepts of “threshold” and “porosity” in the work of Stavrides (2010, 2014) and the discussion on cultural creativity by Favole (2010), Liep (2001) and Wagner (1992). Based on the results of fieldwork carried in Athens for two months in 2015, the analysis focuses on three practices of creation of the common emerged in the Greek capital in recent years: the Navarinou Park, the Agros Elliniko and the Free Self-Managed Theatre Embros. The context where these common spaces have emerged is a city characterized by social injustice produced by the streak power of economic and managerial elites. Common spaces emerge therefore as forms of collective creativity when facing the abstract logics of streaks.